Analyzing Patterns of Classroom Interaction In An Elementary English Online Teaching and Learning Processes - Vineki Riyadini, Maria; Basikin, Basikin (English Education Study Program STKIP PGRI Pacitan, 2024)
Interaction plays a pivotal role in English teaching and learning processes. The patterns of interactions in classroom activities highly influence the success of the teaching-learning process. This study aimed to describe the classroom interaction patterns in an online teaching and learning process through a qualitative approach using the Flanders' Interaction Analysis System (FIAS). This study is focused on the young learner classroom interaction at the elementary school level. An English online class was observed and recorded to collect the data. The data were confirmed by interviewing the English teacher. The findings revealed that the dominant patterns of interaction that emerged in the online teaching and learning processes were asking questions (Teacher's Talk) and giving responses (Students' Talk). The patterns of interaction were produced from teacher and student(s) and student(s) and student(s) interactions concerning the teacher talk and the students' talk categories used in the online teaching and learning activities. By understanding classroom interaction patterns, the results can be worth considering in selecting activities to support students in improving their full potential in teaching and learning processes. Besides, classroom interaction plays a crucial role in achieving the intended goals in the teaching and learning processes.